Macroeconomics - Blanchard, Olivier (Olivier J.) (Prentice Hall series in economics, 2000)
Using words, graphs and algebra, Olivier Blanchard presents an integrated view of macroeconomics. All of the material included in this student text is presented within the context of real world applications.